Competences in Information Management (IMC), in the Training of Public Accountants - Calderón Carmona, Gloria Patricia; Gómez Suárez, Aída Mercedes (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2023)
OBJECTIVE: To address the study of information management competencies [IMC], required for the Public Accountant, going beyond the idea of ​​training in the management of tools or as a user of them and moving on to those competencies that a student is expected to obtain during its formation and after it.MATERIAL AND METHOD: The approach used was qualitative and the type of study was action research. Because it is related to the educational practice, it favored directing the work towards the observation, description and understanding of the experiences and needs of the participants.RESULTS: This research identified the current IMC of Tadeistas public accounting students. Based on the findings and conclusions, a proposal for its development and consolidation supported by ICT was formulated and implemented, framed in the access, organization, use and evaluation of information, and addressing technical and functional, managerial, personal, interpersonal, and communication.CONCLUSIONS: Within the framework of accounting as an information and communication system, it is essential to develop and consolidate these competencies in order to increase the relevance of the information it prepares and its usefulness for stakeholders and their decision-making processes.
Keywords: Information literacy; Competences; Public accountants; Information; Technologies.